A Miniature Four-Hole Probe for Measurement of Three-Dimensional Flow with Large Gradients. (2nd September 2014) - Jangir, Ravirai; Sitaram, Nekkanti; Gajanan, Ct
Abstract : A miniature four-hole probe with a sensing area of 1.284 mm 2 to minimise the measurement errors due to the large pressure and velocity gradients that occur in highly three-dimensional turbomachinery flows is designed, fabricated, calibrated, and validated. The probe has good spatial resolution in two directions, thus minimising spatial and flow gradient errors. The probe is calibrated in an open jet calibration tunnel at a velocity of 50 m/s in yaw and pitch angles range of ±40 degrees with an interval of 5 degrees. The calibration coefficients are defined, determined, and presented. Sensitivity coefficients are also calculated and presented. A lookup table method is used to determine the four unknown quantities, namely, total and static pressures and flow angles. The maximum absolute errors in yaw and pitch angles are 2.4 and 1.3 deg., respectively. The maximum absolute errors in total, static, and dynamic pressures are 3.4, 3.9, and 4.9% of the dynamic pressures, respectively. Measurements made with this probe, a conventional five-hole probe and a miniature Pitot probe across a calibration section, demonstrated that the errors due to gradient and surface proximity for this probe are considerably reduced compared to the five-hole probe.